(untitled) (Journal of Universal Science Research, 2023)
This article describes the activities of the chairmen and deputy chairmen of the existing neighborhoods in Karshi, as well as the issues of providing social services in the neighborhoods and raising the service of helping families in need of social protection to a new level, and further accelerating the work of training women for professions.